Bringing the uncultivated microbial majority of freshwater ecosystems into culture - Salcher, Michaela M; Layoun, Paul; Fernandes, Clafy; Chiriac, Maria-Cecilia; Bulzu, Paul-Adrian; Ghai, Rohit; Shabarova, Tanja; Lanta, Vojtech; Callieri, Cristiana; Sonntag, Bettina; Posch, Thomas; Lepori, Fabio; et al. (Nature communications, 2025)
Axenic cultures are essential for studying microbial ecology, evolution, and genomics. Despite the importance of pure cultures, public culture collections are biased towards fast-growing copiotrophs, while many abundant aquatic prokaryotes remain uncultured due to uncharacterized growth requirements and oligotrophic lifestyles. Here, we applied high-throughput dilution-to-extinction cultivation using defined media that mimic natural conditions to samples from 14 Central European lakes, yielding 627 axenic strains. These cultures include 15 genera among the 30 most abundant freshwater bacteria identified via metagenomics, collectively representing up to 72% of genera detected in the original samples (average 40%) and are widespread in freshwater systems globally. Genome-sequenced strains are closely related to metagenome-assembled genomes (MAGs) from the same samples, many of which remain undescribed. We propose a classification of several novel families, genera, and species, including many slowly growing, genome-streamlined oligotrophs that are notoriously underrepresented in public repositories. Our large-scale initiative to cultivate the "uncultivated microbial majority" has yielded a valuable collection of abundant freshwater microbes, characterized by diverse metabolic pathways and lifestyles. This culture collection includes promising candidates for oligotrophic model organisms, suitable for a wide array of ecological studies aimed at advancing our ecological and functional understanding of dominant, yet previously uncultured, taxa.
Keywords: ekosystém; Metagenome; Lakes; Phylogeny; genom bakteriální; Genome, Bacterial; Metagenomics; Ecosystem; fylogeneze; jezera; sladká voda; Bacteria; metagenomika; Fresh Water; metagenom